Design of CMOS RMS-to-DC converter and timing generator for pin electronics application - Sun, Jing. (2008)
The goal of this research is to explore the design of a pure analog CMOS RMS-to-DC converter and a high-speed, high-resolution CMOS timing generator. For the RMS-to-DC converter, a novel implicit approach will be investigated, which is implemented by current-mode translinear circuits.